The vertical thickness of Jupiter's Europa gas torus from charged particle measurements. Issue 18 (23rd September 2016) - Kollmann, P.; Paranicas, C.; Clark, G.; Roussos, E.; Lagg, A.; Krupp, N.
Abstract: Measurements and modeling suggest the presence of a neutral gas torus collocated with the orbit of Jupiter's moon Europa. Here we use data from the CMS instrument that is part of the Energetic Particles Detector (EPD) on board the Galileo spacecraft to characterize the distribution of 130 keV protons. Near the orbit of Europa this distribution has a minimum around 70° in equatorial pitch angle. We reproduce this with a model assuming that the protons are lost via charge exchange with a gas torus. Since the pitch angle characterizes whether the protons remain mostly in the dense center of the torus or continuously bounce through it, we can determine the latitudinal extent of the torus. We find that the full thickness where its density falls to 1/ e of its maximum has to be ≲ 2 R J and is closer to ≈1 R J . Key Points: Energetic proton intensity dropouts observed by the Galileo mission confirm the presence of the Europa gas torus The Europa torus has a vertical thickness of about 1 R J